2018
DOI: 10.1186/s13045-018-0618-0
|View full text |Cite
|
Sign up to set email alerts
|

miR-519a enhances chemosensitivity and promotes autophagy in glioblastoma by targeting STAT3/Bcl2 signaling pathway

Abstract: BackgroundChemoresistance to temozolomide (TMZ) is a major challenge in the treatment of glioblastoma (GBM). We previously found that miR-519a functions as a tumor suppressor in glioma by targeting the signal transducer and activator of transcription 3 (STAT3)-mediated autophagy oncogenic pathway. Here, we investigated the effects of miR-519a on TMZ chemosensitivity and autophagy in GBM cells. Furthermore, the underlying molecular mechanisms and signaling pathways were explored.MethodsIn the present study, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(102 citation statements)
references
References 46 publications
4
98
0
Order By: Relevance
“…Analogous with our results, knockdown of GAS5 causes tamoxifen resistance and reduces the chemotherapeutic effect of dendrosomal curcumin in breast cancer cells. 10 Intriguingly, our finding substantiated that elevation of GAS5 antagonized the activation of autophagy in cisplatin-exposed cells. 23 Further mechanism analysis conferred that exposure to cisplatin evoked excessive autophagy by increasing the conversion of LC3I to LC3II and suppressing p62 accumulation, both markers to evaluate autophagic flux.…”
Section: Gas5 Mutes Cisplatin-activated Autophagy In a Mtor-dependesupporting
confidence: 71%
See 1 more Smart Citation
“…Analogous with our results, knockdown of GAS5 causes tamoxifen resistance and reduces the chemotherapeutic effect of dendrosomal curcumin in breast cancer cells. 10 Intriguingly, our finding substantiated that elevation of GAS5 antagonized the activation of autophagy in cisplatin-exposed cells. 23 Further mechanism analysis conferred that exposure to cisplatin evoked excessive autophagy by increasing the conversion of LC3I to LC3II and suppressing p62 accumulation, both markers to evaluate autophagic flux.…”
Section: Gas5 Mutes Cisplatin-activated Autophagy In a Mtor-dependesupporting
confidence: 71%
“…9 Analogously, targeting endoplasmic reticulum stress-mediated autophagy elevates the effectiveness of sunitinib and gemcitabine on pancreatic cancer. 10 However, several lines of research have confirmed the protective roles of autophagy in glioma cell growth during chemotherapy. 8 Similarly, overexpression of miR-519a promotes autophagy in glioblastoma and then sensitizes the cell to chemotherapy.…”
mentioning
confidence: 99%
“…The role of autophagy in GBM cells in response to metabolic and therapeutic stress seems to be different, including prosurvival and prodeath (22). Moreover, accumulating evidence has revealed a positive correlation between chemoresistance and autophagy reduction in GBM cells (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-200a, an anti-Galphai1 miRNA, downregulation in human glioma and involved cell proliferation of glioma [17]. miR-519a, as a tumour suppressor, promotes autophagy in glioma [18]. miR-181a was reported to reduce cell proliferation and invasion in glioma [19].…”
Section: Introductionmentioning
confidence: 99%